A nationwide survey on the management of the COVID-19 pandemic and respiratory disease in South Korea - Ang, Lin; Yim, Mi Hong; Song, Eunhye; Lee, Hye Won; Lee, Hyangsook; Kim, Tae-Hun; Willcox, Merlin; Hu, Xiao-Yang; Houriet, Joelle; Graz, Bertrand; Lee, Je-Won; Jang, Yunho; et al. (Frontiers in Medicine, 2022)
Background: This study aimed to investigate individual prevalence of respiratory symptoms during the pandemic and to describe their treatment approaches, preventive health behaviors, and mental health conditions, as well as their associations to COVID-19 infection. Methods: We analyzed responses from an online nationwide survey, conducted between February 2021 to May 2021, about people’s experience during the pandemic. Statistical analysis was also performed to see if there were any significant differences in treatment and prevention strategies between different groups of respondents. Results: A total of 2177 survey respondents completed the survey. The most frequently reported respiratory infections related symptoms were runny or blocked nose (47.55%), cough (45.45%), fever (44.06%), sore throat (41.96%), and fatigue (30.07%). More than half of the respondents used complementary and alternative medicine (CAM) approaches as means of preventive measures. In terms of preventive behaviors, the more emphasized behaviors were mask-wearing and hand-washing behavior. Majority of the respondents did not show signs of mental health issue. Conclusion: This is the first study to look into the diverse physical, psychological, and patient experiences in South Korea during the continuing COVID-19 pandemic. Future COVID-19 and pandemic planning should take individual’s experiences into consideration.